2018
DOI: 10.2174/1389450118666170913162147
|View full text |Cite
|
Sign up to set email alerts
|

Phytomedicines are Efficient Complementary Therapies for the Treatment of Atopic Dermatitis: A Review of Mechanistic Insight and Recent Updates

Abstract: In conclusion, herbal medicines hold great promise as complementary and alternative therapies for the treatment of mild-to-moderate AD when used as monotherapy and for the treatment of moderate-to-severe AD when used in conjunction with other pharmacological agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Additionally, oral utilization of XG and PP in adults demonstrated no systemic adverse events during 6 months of treatment [ 43 , 44 ]. To date, the literature revealed that phytotherapeutic treatments for AD and products of natural origin are often considered adjunctive therapies for the treatment of moderate to severe AD [ 18 , 45 ]. Clinical trials assessing the efficacy and safety of topical phytotherapy for AD treatment are limited.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, oral utilization of XG and PP in adults demonstrated no systemic adverse events during 6 months of treatment [ 43 , 44 ]. To date, the literature revealed that phytotherapeutic treatments for AD and products of natural origin are often considered adjunctive therapies for the treatment of moderate to severe AD [ 18 , 45 ]. Clinical trials assessing the efficacy and safety of topical phytotherapy for AD treatment are limited.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the European Scientific Cooperative on Phytotherapy (ESCOP), phytotherapy corresponds to the science of the medicinal use of plants and herbal products for the prevention and treatment of diseases [17]. Phytopharmaceuticals are used for an extensive range of conditions, such as hypertension [18], atopic dermatitis [19], and depression [20]. In terms of respiratory tract infections, a cross-sectional survey of 250 parents from Turkey revealed that the prevalence of non-drug therapeutic approaches used for their children with symptoms of viral URIs was 47.2%, and that the most common approach was herbal tea (prevalence of 30.5%) [21].…”
Section: Introductionmentioning
confidence: 99%